Organisational learning in a fusion school - Laiho-Murdoch, Heli (2016)
Laiho-Murdoch, Heli. 2016. Organisational learning in a Fusion School University of Jyväskylä. Department of Education. This empirical research examines organisational learning in a fusion-school development during the period of 2010 and 2012 by a case study approach of the phenomenon. This educational fusion is between two diverse countries; Finland and the United Arab Emirates. The background is Abu Dhabi’s education reform since 2003 and the Finnish outstanding educational experience and excellent PISA results. The originality value of this research is unique. This partnership is first of its kind in Finland, and has therefore notable interest value. Organisational learning manifesting in this type of education partnership fusion has not been researched before and to my true knowledge has not been reported elsewhere, so this study is significant. I was immersed into the empirical social-world of the process and the life as a participant observer. I chose five applicable theories that enable me to explain the organisational learning in school environments, open up organisational learning concepts via literature and examine the organisational learning in the fusion school. In the light of these theories I proceed to a deductive qualitative analysis of the phenomenon. Data was collected in team meetings, innovation workshops, staff meetings, in informal and semi-structured teacher interviews, teacher observations, and collegial discussions over two years. As organisational learning promote detection and correction of error and help avoiding behaviours that preserve status quo permitting proactive learning, embedding new knowledge, enabling school systems to renew or transform and balance continuity and change (Collinson & Cook, 2007, p. 45) this research will support the fusion regeneration process. The data reveals areas of professional development need to ensure organisational learning growth.